Raman response function and supercontinuum generation in chalcogenide fiber - Hu, Jonathan; Menyuk, Curtis; Shaw, L. B.; Sanghera, J. S.; Aggarwal, I. D. (Optica, 2008)
We show the Raman response function and dispersion curve for a chalcogenide fiber. We then model and reproduce the experimental bandwidth of IR supercontinuum generation using a chalcogenide PCF.
Conference on Lasers and Electro-Optics 2008, San Jose, California United States, 4–9 May 2008
Keywords: Femtosecond lasers; Photonic crystal fibers; UMBC Optical Fiber Communications Laboratory; UMBC High Performance Computing Facility (HPCF); Supercontinuum generation; Chalcogenide glass; Optical fibers; Silica fibers; UMBC Optical Fiber Communications Laboratory